PENGARUH PERMAINAN PLAYDOUGH TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK HEAVEN KID’S KECAMATAN TAMPAN KOTA PEKANBARU - Dewi Rohana; Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the fine motor skills of children aged 5-6 years in kindergarten Heaven Kid's subdistrict Handsome Pekanbaru City before the game playdough, To determine the fine motor skills of children aged 5-6 years in kindergarten Heaven Kid's subdistrict Handsome Pekanbaru City after done playdough game, to determine whether there is influence playdough game against the fine motor skills of children aged 5-6 years in kindergarten Heaven kid's Handsome District of Pekanbaru city, to determine how much influence the game playdough fine motor skills of children aged 5-6 years in kindergarten Heaven kid's subdistrict handsome Pekanbaru. Samples were all children aged 5-6 years in kindergarten Heaven Kid's Pekanbaru as many as 17 children. Data collection technique used observation sheet that contains fine motor skills of children. Based on the results of this study concluded prior to the treatment given are in the low category 10 children or 58.8% in the moderate category 7 children, or 41.2%, and there are no children in the high category. It can be seen that after treatment (treatment), fine motor skills of children has increased that there are children who are in the high category as many as 12 children, or 70.59%, and there are children who are in the moderate category 5 children or 29.41% and there are children in the category of low or 0%. This shows that there is influence of playdough game against the fine motor skills.Keywords: Fine Motor Ability, Playdough game.